5 questions on Agile - Brush, Michelle; Foster, Brian (O'Reilly, 2018)
"In this interview, Content Director Brian Foster talks to Michelle Brush about how Cerner applies Agile practices. Michelle Brush is a math geek turned computer geek. She has developed algorithms and data structures for search, compression, and data mining in embedded as well as enterprise systems. In her current role as a senior software architect for Cerner Corporation, she manages and mentors software engineers and architects on test-driven development, software architecture, code quality, and communication. Five Questions is a series where we sit down with leading industry practitioners and ask them for real-world stories and examples of how they're using technology in their everyday work."--Resource description page